Profil Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Higher Order Thinking Skills pada Materi Pola Bilangan - Lestari, Puput Puji; Anggraini, Anggraini; Sugita, Gandung; Murdiana, I Nyoman (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to describe students' critical thinking skills in solving HOTS questions on number pattern material in class VIII SMPN 12 Palu. The method used in this research is qualitative method. The results showed that students with high ability (S1) were able to fulfill all stages of critical thinking well, including clarification, assessment, inference, and strategy in solving number pattern problems. Students with moderate ability (S2) showed varied abilities, with deficiencies mainly at the strategy stage. Meanwhile, students with low ability (S3) experienced significant difficulties in the clarification, inference and strategy stages, which affected the results of solving problems that were less precise. The conclusion is that students with high ability (S1) in mathematics show good critical thinking skills at all stages of problem solving, while students with moderate ability (S2) show variability and students with low ability (S3) face difficulties in several aspects of critical thinking, especially in understanding problem information, inference and solution strategies. Keywords: Critical Thinking Ability, Number Patterns, HOTS Questions